Stem cell properties of cancer cells in ascitic fluid of patients with ovarian cancer: a key to control over cancer progression - O. I. Kovalev; S. V. Vtorushin; E. V. Kaigorodova (Бюллетень сибирской медицины)
Ovarian cancer is considered to be the most malignant and aggressive tumor of the female reproductive system, which is largely associated with early development of malignant ascites and peritoneal carcinomatosis. Cancer cells representing the primary focus, as well as those contained in the ascitic fluid, are extremely heterogeneous in terms of morphological, immunohistochemical, and molecular genetic aspects. Cancer stem cells play a significant role in tumor self-renewal, differentiation, metastasis, and development of chemoresistance.This literature review is aimed at summarizing the available data on cancer stem cells in ovarian cancer and their role in tumor progression. A bioinformatic search was carried out in the PubMed, NCBI, Google Scholar, and eLibrary databases using the keywords “cancer stem cells”, “ovarian cancer”, “malignant ascites”, “chemoresistance”, etc.The data presented in the review make it possible to comprehensively characterize the role of stem cell properties of ovarian cancer cells. The review presents up-to-date information on the molecular and biological parameters of cancer stem cells in ovarian cancer, which are the cellular component of malignant ascites, as well as data from the authors’ studies. Along with this, the article describes modern ideas about the mechanisms of formation of cellular spheroids and their contribution to cancer progression.Cancer stem cells are an extremely promising target in the development of future therapeutic strategies based on the study of signaling pathways in ovarian cancer stem cells, the mechanisms of spheroid formation, and the contribution of immune cells to the acquisition of cancer stem cell properties.